2021
DOI: 10.4236/ojd.2021.102004
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Item Who Well-Being Index as a Screening Tool for Depression in a Population of Doctors and Nurses in Nigeria during the COVID-19 Pandemic

Abstract: Background: Undetected depression can result in a significant decline in productivity among the workforce in every system, the healthcare sector inclusive. It is vital to utilize brief screening tools to detect populations at risk of depression. The 5-item WHO Well-being Index (WHO-5) has been used as a screening measure for depression, but research on this is scarce in sub-Saharan Africa. This study aimed to determine the utility and validity of the WHO-5 in screening for depression in a population of doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These results are indications that the one-factor structure estimates better regarding the well-being of adolescents. These findings are in agreement with previous validation studies [ 14 , 20 , 39 , 42 , 43 , 46 , 48 ]. This implies that the well-being of adolescents in Ghana could be explained by a single underlying trait likewise adolescents of other countries.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are indications that the one-factor structure estimates better regarding the well-being of adolescents. These findings are in agreement with previous validation studies [ 14 , 20 , 39 , 42 , 43 , 46 , 48 ]. This implies that the well-being of adolescents in Ghana could be explained by a single underlying trait likewise adolescents of other countries.…”
Section: Discussionsupporting
confidence: 94%
“…Numerous studies have assessed the validity and psychometric properties of the WHO-5 well-being index across different geographical contexts such as in Europe [ 35 , 39 , 40 ], Asia [ 41 , 42 , 43 , 44 ], and Africa [ 45 , 46 ]. For example, in Europe, Sischka et al [ 35 ] used item response theory and the analysis of measurement invariance across 35 countries and discovered that the model appropriately fitted the data for all countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the WHO-5 questionnaire is not designed to definitely diagnose depressive disorders, thus, further investigation should be considered. Besides, several other studies have proven the validity and reliability of the WHO-5 questionnaire (Seb-Akahomen et al, 2021).…”
Section: Reliability Of Who-5 Questionnairementioning
confidence: 99%
“…Beyond its usefulness in the measurement and monitoring of well-being, the WHO-5 was found to be one of the main measures which has extensively demonstrated su cient validity to screen for and early detect depression in different clinical and non-clinical populations across several settings, cultures and countries. Indeed, the WHO-5 showed clinical utility in the screening for depressive symptoms in community adults [29][30][31], university students [32], healthcare workers during the COVID-19 [33], older adults residing in nursing homes [34], as well as in various clinical populations, including patients with diabetes [35][36][37][38], people diagnosed with Parkinson's disease [39], cardiac patients [40], acne vulgaris patients [41], child and adolescent patients from pediatric hospitals [42], and adolescents with major depressive disorder [43]. A systematic review of the literature by Topp et al [23] encompassing 213 studies revealed that the WHO-5 is sensitive and speci c screening instrument for depression, and has a very high applicability across research elds.…”
Section: The Psychometric Potential Of the Who-5 In Patients With Sch...mentioning
confidence: 99%